STUDENT APPRECIATION OF MEDICAL RESEARCH IN UNDERGRADUATE. MULTICENTER STUDY IN 19 UNIVERSITIES - Nakandakari, Mayron D. (2019)
Objective: To know the appreciation of the student on the work of the Peruvian scientific research universities medical undergraduate students of faculties of medicine of the Peru, 2016-2017. Methods: It is a multicentric, observational, descriptive and transversal study. It featured the participation of 400 medical students belonging to 19 faculties of medicine officially recognized by the Peruvian Association of faculties of Medicine (ASPEFAM). Applied sampling was not probabilistic. A validated by a study earlier, auto-applicative, anonymous, voluntary survey was used, and which underwent a pilot test. The collection was virtual and the analysis was descriptive. Results: Only 7,8% concerned that its faculty of medicine Yes supported research. Around 56% concerned do not feel sufficiently trained by their University to achieve the scientific publication in biomedical journals. And most they did appreciate that their universities do not encourage the seed research, do not have scientific internships and there is support for students to execute or carry out their thesis. Conclusions: The perceptions of the students about the work of universities in undergraduate scientific medical research, it was classified as "deficient" by the majority of the surveyed.